Romance languages and linguistic theory 2009 : selected papers from "Going Romance" Nice 2009 - Berns, Janine; Jacobs, Haike, 1961-; Scheer, Tobias, 1968- (Romance languages and linguistic theory (RLLT) ;, 2011)
The annual Going Romance conference has developed into the major European discussion forum for theoretically relevant research on Romance languages where current ideas about language in general and about Romance languages in particular are tested. The twenty-third Going Romance conference was a very special one: for the first time it was not hosted by one of the Dutch universities, but was co-organized by the Radboud University Nijmegen and the Université de Nice-Sophia Antipolis and held in France at the Maison du Séminaire in Nice from 3-5 December 2009. The present volume contains a broad r.